2023
DOI: 10.3390/ijms24119649
|View full text |Cite
|
Sign up to set email alerts
|

The Curcumin Analog PAC Is a Potential Solution for the Treatment of Triple-Negative Breast Cancer by Modulating the Gene Expression of DNA Repair Pathways

Esraa Almalki,
Abdullah Al-Amri,
Reem Alrashed
et al.

Abstract: Breast Cancer (BC) is one of the most common and challenging cancers among females worldwide. Conventional treatments for oral cancer rely on the use of radiology and surgery accompanied by chemotherapy. Chemotherapy presents many side effects, and the cells often develop resistance to this chemotherapy. It will be urgent to adopt alternative or complementary treatment strategies that are new and more effective without these negative effects to improve the well-being of patients. A substantial number of epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
0
0
Order By: Relevance
“…This finding reflected inhibition of the CXCL12/ CXCR4 axis [130]. The curcumin analog, PAC, was shown to inhibit BC by modulating DNA repair pathway gene expression [131]. Of note, a series of studies have demonstrated that curcumin has a pivotal role in augmenting the therapeutic efficiency of chemotherapy drugs in BC [132][133][134].…”
Section: Curcuminmentioning
confidence: 99%
“…This finding reflected inhibition of the CXCL12/ CXCR4 axis [130]. The curcumin analog, PAC, was shown to inhibit BC by modulating DNA repair pathway gene expression [131]. Of note, a series of studies have demonstrated that curcumin has a pivotal role in augmenting the therapeutic efficiency of chemotherapy drugs in BC [132][133][134].…”
Section: Curcuminmentioning
confidence: 99%